Identificação de genes e vias moduladas na Síndrome de Guillian-Barré em bibliotecas transcriptômicas - Moreira, Raulzito Fernandes (2018)
Guillain-Barré syndrome (GBS) is an acute polyradiculoneuropathy, monophasic, and since the eradication of poliomyelitis is the principal cause of paralysis in the world. This syndrome seems to have an autoimmune component characterized, in part, by molecular mimicry with production of antibodies that causes severe damage to peripheral nerves. Such damage results in symptoms, which include acute flaccid paralysis. About 30% of the cases need respiratory assistance. GBS cases is usually preceded by infection agents, such as Campylobacter jejuni and viral infections. It seems that the pathogenesis of C. jejuni in GBS is associated with anti-gangliosides antibodies, which cross react with gangliosides present in the nerve axolemma, mainly in the peripheral nerves. Hence, the present study aimed to analyze transcriptomic libraries from patients with GBS, diagnosed with the different subtypes (demyelinating, axonal and Miller-Fisher), in order to identify genes and key pathways related to GBS development and potential target for modulation. For this, 24 libraries were obtained from 12 Brazilian cases and a Spanish case. The quality analysis, alignment, assembly, global gene expression and network were performed using FastQC, Bowtie, TopHat, HTSeq, edgeR and RedeR. We idenfy genes were differentially expressed between symptomatic and the recovery phase (p<0.01 and fold change 1). Transcript annotation based on GO and KEGG terms showed changes in expression of genes related to inflammation, as Jak-STAT, B and T cell receptor signaling, Toll-like, in addition to IgG immunoglobulins and associated receptors. Also, pathways related to neurodegenerative, autoimmune and infectious diseases were enriched during symptomatic phase when compared to recovery phase. We suggest EGR2, HBGF e SIGLEC1 as potentials progression biomarkers in SGB and therapeutic targets. These results provide an overview of possible responses during the course of GBS.